Nghiên cứu phản ứng khâu mạch quang hóa của một số hệ khâu mạch quang trên cơ sở glyxydyl ete của nhựa o-crezolfomandehyt. I - Ảnh hưởng của tỷ lệ chất khơi mào quang cation TAS đên phản ứng khâu mạch quang hóa của hệ CG-BCDE-TAS - Hiền, Lê Xuân; Ngọc Minh, Đỗ Thị; Ngọc Minh, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The influence of the content of cationic photoinitiator–triarylsulfonium salt (TAS) on the photocrosslinking of the systems containing glyxydyl ete of o-crezolformaldehyde resine (CG), biscycloaliphatic diepoxy monome (BCDE) with the mass ratio CG/BCDE = 1/1 has been studied. The study of the photopolymerization of the epoxy group in the 20 mm thickness film of the system by IR – Spectroscopy in the presence of TAS in the range from 1% to 7% of the total mass of the CG and BCDE showed the fastest convertion rate of the TAS and epoxy groups at the content of TAS 5%, leading to the final convertion of TAS, epoxy groups of BCDE and the total epoxy groups of CG and BCDE 99%, 98% and 82% respectively after exposure under 250 mW/cm2 intensity UV – lamp.